Examining the time dependence of DAMA’s modulation amplitude - Chris Kelso; Christopher Savage; Pearl Sandick; Katherine Freese; Paolo Gondolo (European Physical Journal C: Particles and Fields, 2018)
Abstract If dark matter is composed of weakly interacting particles, Earth’s orbital motion may induce a small annual variation in the rate at which these particles interact in a terrestrial detector. The DAMA collaboration has identified at a $$9.3σ $$ 9.3σ confidence level such an annual modulation in their event rate over two detector iterations, DAMA/NaI and DAMA/LIBRA, each with $$\sim 7$$ ∼7 years of observations. This data is well fit by a constant modulation amplitude for the two iterations of the experiment. We statistically examine the time dependence of the modulation amplitudes, which “by eye” appear to be decreasing with time in certain energy ranges. We perform a chi-squared goodness of fit test of the average modulation amplitudes measured by the two detector iterations which rejects the hypothesis of a consistent modulation amplitude at greater than 80, 96, and 99.6% for the 2–4, 2–5 and 2–6 keVee energy ranges, respectively. We also find that among the 14 annual cycles there are three $$\gtrsim 3σ $$ ≳3σ departures from the average in our estimated data in the 5–6 keVee energy range. In addition, we examined several phenomenological models for the time dependence of the modulation amplitude. Using a maximum likelihood test, we find that descriptions of the modulation amplitude as decreasing with time are preferred over a constant modulation amplitude at anywhere between $$1σ $$ 1σ and $$3σ $$ 3σ , depending on the phenomenological model for the time dependence and the signal energy range considered. A time dependent modulation amplitude is not expected for a dark matter signal, at least for dark matter halo morphologies consistent with the DAMA signal. New data from DAMA/LIBRA–phase2 will certainly aid in determining whether any apparent time dependence is a real effect or a statistical fluctuation.